Racing with rhetoric: a Byzantine ekphrasis of a chariot race - Marciniak, Przemysław (Byzantinische Zeitschrift, 2014)
Michael Hagiotheodorites’ poem describing a chariot race is usually dismissed as an imitation of the earlier text composed by Christopher of Mytilene. Such an approach ignores the poetical and rhetorical qualities of Hagiotheodorites’ work, who, in the introduction, skilfully connected the rhetorical framework with the content. The poem is addressed to an unnamed addressee and a definite identification is not possible. However, certain similarities between this text and the works of Constantine Manasses allow a hypothesis that Manasses might have been the recipient of Hagiotheodorites’ letter-poem